Ten-year mortality from coronary heart disease among 172,000 men classified by occupational physical activity. - Menotti, A.; Puddu, V. (Scandinavian Journal of Work, Environment & Health, 1979)
A cohort of 172,489 males aged 20--64 years and employed by the Italian railroad system on 1 April 1963 have been classified by habitual physical activity at work and followed-up for death during a ten-year period. The overall crude mortality was 56.59 per 1,000 in ten years, and no significant differences were found between men in sedentary, moderate and heavy work. Age-corrected death rates for coronary heart disease, as manifested by myocardial infarction and sudden coronary death, were substantially different in the three activity groups, moderately active workers ranking first, sedentary workers second, but very close to the former, and very active workers being last. The age-corrected rates for all ages were 14.18, 12.55 and 7.63 per 1,000 in ten years, respectively. All differences were statistically significant, the mortality ratio between the sedentary and moderate groups combined versus the heavy group being of the order of 1.75 to 1.
Keywords: coronary heart disease; epidemiology; heart disease; man; mortality; occupational physical activity; physical activity; risk factor